The Algorithmic Revolution: How Artificial Intelligence is Transforming Clinical Trials - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The process of bringing a new drug to market is notoriously lengthy, costly, and fraught with uncertainty. Clinical trials, the cornerstone of medical advanc...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation